Iron Bioavailability From Spirulina (Arthrospira Platensis) And Its Interactions With Other Dietary Factors In Vitro And In Vivo - Loh, Su Peng (2004)
Deficiency of iron is common worldwide. Various approaches have been used to improve iron intake and absorption. These include the use of spirulina, a microalage that is already popular in many Asian countries as a functional food supplement. The main objective of this study was to determine the iron bioavailability from spirulina and its interactions with other dietary factors both in vitro and in vivo. In vitro digestion/Caco-2 cell culture system accompanied by either centrifugation or dialysis step was used to assess the availability of iron from spirulina. Using the centrifugation method, the cultured and commercial spirulina yielded significantly higher results (P< 0.05) than then dialysis method, both in the form of iron available for uptake and the actual amount of iron being transported across the Caco-2 cells. The amount of available iron and iron being transported from ferrous sulphate (FeS04) did not differ significantly for both the dialysis and centrifugation method. The effects of different molar ratios of nutrients (calcium, ascorbic acid, zinc, tannic acid and caffeine) to iron on the availability of iron from cultured spirulina differs in comparison with FeS04. In the presence of lower concentrations of calcium (1:5, 1:10, 1:15 and 1:20 Fe:Ca molar ratios), iron from spirulina was not significantly inhibited compared to FeS04 but at higher concentrations (1 :37.34, 1:74.67 and 1:149.34 Fe:Ca molar ratios) iron from both spirulina and FeS04 was significantly inhibited. The availability of iron from spirulina in the presence of ascorbic acid were not significantly enhanced at all the molar ratios tested (1:0.5, 1:1, 1:1.5 and 1:2 Fe:AA molar ratios) whereas iron availability from FeS04 were significantly higher for all the molar ratios. Both zinc and tannic acid were more inhibiting on iron availability from spirulina in comparison to FeS04. As for caffeine, it did not show any significant inhibitory effects on both iron availability from spirulina and FeS04. Two iron pools could coexist in the spirulina, one containing organic iron and another comprising inorganic iron. Organic iron is known to be more bioavailable and less affected by the presence of other nutrients. This could be one of the explanations why the iron from this algae is highly available and its bioavailability is not significantly affected by other nutrients as in FeS04. Haemoglobin repletion assay was used to further investigate the effect of calcium on absorption of iron in spirulina and it comparison with FeS04. In this study, haemoglobin and haematocrit levels of male Sprague-Dawley rats fed both spirulina and FeS04 were found similar although the dose of FeS04 used had twice the amount of iron compared to that in spirulina. The presence of calcium did not significantly reduced the haematological value in rats fed spirulina and FeS04. The percentage of haemoglobin regeneration efficiency (HRE) obtained was significantly higher in rats fed spirulina compared with rats fed FeS04 indicated that the absorption efficiency were better from iron in spirulina compared to iron in FeS04. The distribution study of iron from spirulina and FeS04 in the presence of calcium was done using iron deficient and iron normal male ICR mice fed either spirulina or FeS04 tagged extrinsically with 59Fe. The amount of 59Fe being absorbed by the iron deficient mice fed spirulina was comparable with those fed FeS04 at 6 hand 24 h. However at 7 d, the FeS04 group showed better absorption than the spirulina group. In the iron normal mice, a significantly lower percentage of 59Fe was observed in mice fed spirulina compared to mice fed FeS04 at 6 hand 24 h indicating that iron from spirulina were not readily absorbed in iron normal states, which could prevent iron overload and toxicity. The presence of calcium did not significantly inhibit iron absorption in spirulina as shown in the in vitro study. This study indicated that spirulina is a concentrated source of iron for both supplementation and fortification. Iron from spirulina is highly bioavailable and easily absorbed by the body especially in the iron deficient state. Beside providing the necessary iron, it could also prevent iron overload and toxicity in normal iron status and thus making spirulina suitable for both the iron deficient and normal iron status.